American Whiteness as Perpetual Madness: Don Quixote Through the Lens of Ibram X. Kendiâ€™s Stamped From The Beginning - Oleson, Alice A. (European Scientific Journal, ESJ, 2017)
In Stamped From The Beginning (2016), Ibram X. Kendi provides a typology of the ways in which segregationist racism, assimilationist racism, and anti-racism work in the U.S. through the lives of Cotton Mather, Thomas Jefferson, William Lloyd Garrison, W.E.B. Du Bois, and Angela Davis. Kendiâ€™s book thus offers several lived-in models for probing the reach of Whiteness, racism, and anti-racism in specific places and times rather than in the abstract. The academic abstraction of real-world problems is a danger that Vine Deloria, Jr. discussed as a part of his leadership within the American Indian Movement of the late 1960â€™s and early 1970â€™s. Deloria asked youth to avoid being â€œego-fed by abstract theories and hence unwittingly manipulatedâ€ (1969:84). In the analysis to follow, I apply Kendiâ€™s typology of racist and anti-racist ideas to the novel Don Quixote as a practical work of anti-racism in the subject area of educational equity.